Influence of climate, soil use and soil depth on soil organic carbon content at two Andean altitudinal sites in Norte de Santander, Colombia (2018)
The increase and stabilization of soil organic carbon (SOC) represent a feasible alternative for mitigating greenhouse effect. But, SOC is severely affected by changes in soil use, and there is uncertainty about which types of soil use favor carbon sequestration. In addition, climate influences SOC dynamics; therefore, the effect generated by the use and management of soils is different in cold climates and warm climates. In order to understand how climate, soil use and soil depth influence SOC dynamics at two Andean sites in Norte de Santander, Colombia, the soil physical (sands, silts, clays, and bulk density) and chemical (pH, E.C., C.E.C. and S.B) properties were studied. Also, the total organic carbon (TOC), light fraction (LF), humic fraction (HF), microbiol biomass (MB) and organic carbon were measured. These evaluations were performed in two climates (cold and warm), with three soil uses per climate and three soil depths (0 to 5 cm, 5 to 10 cm and 10 to 20 cm). The amount of organic carbon was statistically higher in the cold climate soils for all compartments (TOC, OC of MB, OC of LF and OC of HF). The Forest and Pasture were more favorable for SOC storage in the cold climates, and the intensive crops presented a lower content of TOC, OC of MB and OC of LF. The humification rate and OC of HF were higher in the soils with intensive crops as the soil use in the warm climate.